Determinant Teenager Family Planning in Banten Province 2019 (SKAP 2019 Secondary Analysis Data) - Reni Nofita; Dorsinta Siallagan; Restu Octasila; Rd. Deden Gumilar Nugraha (Universitas Aisyah Pringsewu, 2022)
The United Nations Children's Fund (UNICEF) in 2013, stated that Indonesia was the country with the seventh-highest child marriage rate in the world. Based on data SKAP 2019, the knowledge index of adolescents about KRR for Banten Province at 44.2%. The purpose of the study was to determine the determinants of family planning in teenagers in Banten Province in 2019 as input in determining the priority of improvement program efforts in reducing the incidence of early marriage in adolescents, especially in Banten Province. This research is a quantitative study, using secondary data from the 2019 Youth SKAP. The research design is cross sectional. The outcome variable of this study is family planning in adolescents, while the predictor variables include; Gender, area of residence, education, age group, teenager Knowledge about Reproductive Health, Exposure to media sources, Information Source Officer, Ever Dating, Sexual Attitude before marriage and Courtship Behavior. The population of this study was teenagers in Banten Province, while the research sample used the results of the 2019 SRS SKAP data restriction, namely 1454 respondents. Univariate analysis describes family planning in teenagers and their predictor factors, bivariate analysis using Chisquare and Anova, for multivariate analysis using logistic regression. The results obtained 59.6% of family planning in teenagers is not good. There was a significant relationship between age group (p=0.001), place of residence (p= 0.000), level of education (p=0.000), knowledge of adolescent reproductive health (p=0.000), exposure to information media (p=0.000), service provider information (p=0.000), ever dating (p=0.000) and courtship behavior (p=0.000) on family planning in adolescents in Banten Province in 2019. The most dominant factor for family planning in teenager is teenager knowledge about reproductive health in the category of having sufficient the chances of family planning are 7 times better than those with less good knowledge after being controlled by variables of age group, place of residence, education level, media exposure, information giving officers and having been in a relationship. Suggestions for this research to the youth sub-sector to continue to disseminate information about teenager reproductive health either through the media or officers who provide information and make advertisements about reproductive health or family planning. Abstrak: The United Nations Children's Fund (UNICEF) pada tahun 2013, menyatakan bahwa Indonesia menjadi negara dengan angka perkawinan anak tertinggi ketujuh di dunia. Berdasarkan data SKAP 2019 tentang indek pengetahuan remaja tentang KRR untuk Provinsi Banten pada angka 44,2%. Tujuan penelitian adalah Diketahuinya determinan perencanaan keluarga pada remaja di Provinsi Banten Tahun 2019 sebagai bahan masukan dalam menentukan prioritas upaya program peningkatan dalam mengurangi kejadian nikah dini pada remaja khususnya di Provinsi Banten. Penelitian merupakan studi kuantitatif, menggunakan data sekunder SKAP Remaja 2019. Desain Penelitian cross sectional. Variabel outcome penelitian ini adalah perencanaan keluarga pada remaja, sedangkan variable predictor meliputi; Jenis kelamin, wilayah tempat tinggal, pendidikan, kelompok umur, Pengetahuan Remaja tentang kesehatan Reproduksi, Keterpaparan sumber media, Petugas Sumber Informasi, Pernah Pacaran, Sikap Seksual sebelum menikah dan Perilaku pacaran. Populasi penelitian ini adalah remaja di Provinsi Banten sedangkan sampel penelitian menggunakan hasil retriksi data SRS SKAP 2019 yaitu 1454 Responden. Analisa univariat menggambarkan perencanaan keluarga pada remaja serta factor-faktor prediktornya, analisa bivariate menggunakan Chisquare dan Anova, untuk analisa multivariate menggunakan regresi logistik. Hasil diperoleh 59.6 % perencanaan keluarga pada remaja kurang baik. Terdapat hubungan signifikan antara kelompok usia (p= 0.001), tempat tinggal (p= 0.000), tingkat pendidikan (p=0.000), pengetahuan tentang kesehatan reproduksi remaja (p=0.000), Keterpaparan Media informasi (p=0.000), petugas pemberi informasi (p=0.000), pernah pacaran (p=0.000) dan perilaku pacaran (p=0.000) terhadap perencanaan berkeluarga pada remaja di Provinsi Banten Tahun 2019. Faktor yang paling dominan terhadap perencanaan berkeluarga pada remaja pengetahuan remaja tentang kesehatan reproduksi katagori cukup memiliki peluang perencanaan keluarga 7 kali lebih baik dibandingkan berpengetahuan kurang baik setelah dikontrol oleh variabel kelompok usia, tempat tinggal, tingkat pendidikan, keterpaparan media, petugas pemberi informasi dan pernah pacaran. Saran penelitian ini kepada Sub bidang remaja agar tetap menyebarkan informasi tentang kesehatan reproduksi remaja baik melalui media ataupun petugas pemberi informasi serta membuat iklan mengenai kesehatan reproduksi atau perencanaan berkeluarga.